Nigeria’s Tax Reforms and the Quest for Economic Stability: A Conceptual Narration - Kirfi, Musa Mohammed; Aliyu, Almustapha A.; Solomon, Othniel (Kashere Journal of Politics and International Relations, 2025)
This study explores the relationship between Nigeria’s tax reform bill and economic stability, providing a conceptual narration of the potential impacts of tax reform on the nation’s economic growth and development. The study examines the current tax regime in Nigeria, highlighting its limitations and challenges, and analyzes the proposed tax reform bill’s potential to address these issues. The study investigates how tax reform can influence economic stability through various channels, including increased revenue generation, improved investment climate, and enhanced economic competitiveness. It also discusses the potential challenges and limitations of implementing tax reform in Nigeria, such as resistance from special interest groups and administrative capacity constraints. Using a conceptual framework that integrates tax theory and economic stability, this study provides a nuanced understanding of the complex relationships between tax policy, economic growth, and development. The project contributes to the ongoing debate on tax reform in Nigeria, offering insights into the potential benefits and challenges of reforming the tax system to achieve economic stability. The findings of this study have implications for policymakers, researchers, and stakeholders interested in Nigeria’s economic development. The project concludes by highlighting the need for a comprehensive and inclusive tax reform process that addresses the country’s unique economic challenges and promotes sustainable economic growth and development. By striking a balance, taxation can support economic stability and promote sustainable development because they are interconnected. Ultimately, this study aims to inform and enrich the discourse on tax reforms and economic stability in Nigeria.